Development of amorphous carbon protective coatings on poly(vinyl)chloride - Rangel, Elidiane C. [UNESP]; de Souza, Eduardo S. [UNESP]; de Moraes, Francine S. [UNESP]; Marins, Nazir M. S. [UNESP]; Schreiner, Wido H.; Cruz, Nilson C. [UNESP] (Elsevier B.V. Sa, 2010)
The great versatility of polymers has promoted their application in a series of ordinary situations. The development of specific devices from polymers, however, requires modifications to fit specific stipulations. In this work the surface properties of thin films grown onto polyvinylchloride (PVC) were investigated. Hydrogenated amorphous carbon films were deposited onto commercial PVC plates from acetylene and argon plasmas excited by radiofrequency (13.56 MHz, 70 W) power. The proportion of acetylene in the gas feed was varied against that of argon, keeping the total pressure constant at 2.5 Pa. Deposition time was 1800 s. Film elemental composition was analyzed by X-ray photoelectron spectroscopy, XPS. Water contact angle measurements were performed using the sessile drop technique. The root mean squared roughness was derived from 50 x 50 mu m(2) surface topographic images, acquired by scanning probe microscopy. Nanoindentation and pin-on-disk techniques were employed on the determination of film hardness and sliding wear, respectively. Oxidation resistance was obtained through the etching rate of the samples in oxygen radiofrequency (1.3 Pa, SOW) plasmas. From XPS analysis it was detected oxygen and nitrogen contamination in all the samples. It was also found that sp(3)/sp(2) ratio depends on the proportion of argon in the plasma. At lower argon concentrations, hardness, wear and oxidation resistances were all improved with respect to the uncoated PVC. In such conditions, the surface wettability is low indicating a moderate receptivity to water. This combination of properties, ascribed to a balance between the ion bombardment and deposition processes, is suitable for materials exposed to rigorous weathering conditions. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Plasma-enhanced chemical vapor deposition; Hardness; Wettability; Oxidation; Polyvinylchloride; a-C:H; Atomic force microscopy; X-ray photoelection spectroscopy